1993
DOI: 10.1073/pnas.90.3.1068
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced interaction of L-selectin with the high endothelial venule ligand via selectively oxidized sialic acids.

Abstract: The selectins are adhesion receptors that play key roles in leukocyte trafficking. Each has an N-terminal C-type lectin domain that binds to specific carbohydrates in a calcium-dependent manner. L-selectin recognizes sulfated, sialylated ligands on lymph node high endothelial venules. This recognition is abolished by strong periodate oxidation under conditions that destroy oligosaccharides. In contrast, mild periodate oxidation, which selectively oxidizes the side chain of sialic acid residues without affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 35 publications
(43 reference statements)
3
36
0
Order By: Relevance
“…5). These data are consistent with prior studies on the sensitivity of sialoadhesin and CD22 binding to modifications of the sialic acid residue (6, 33, 46 -48) and contrast with studies on selectins, in which extensive modifications of sialic acids have no effect (12,14,49). In fact, substitution of the entire sialic acid (e.g.…”
Section: Figsupporting
confidence: 67%
“…5). These data are consistent with prior studies on the sensitivity of sialoadhesin and CD22 binding to modifications of the sialic acid residue (6, 33, 46 -48) and contrast with studies on selectins, in which extensive modifications of sialic acids have no effect (12,14,49). In fact, substitution of the entire sialic acid (e.g.…”
Section: Figsupporting
confidence: 67%
“…Cover-slips were rinsed extensively in PBS, then stored in 0-16 M ethanolamine, pH 8-3, for at least 24 h at 4 °C in order to saturate free aldehyde groups. After fixation in 1 % paraformaldehyde for 20 min at 4 °C, ethanolamine treatment was not necessary (Norgard et al 1993, data not shown).…”
Section: Endothelial Cellsmentioning
confidence: 94%
“…51 We also used EDTA-containing buffer to confirm that the interactions are calciumdependent and adjusted salt concentrations to more closely approximate the physiological state. 53 Although some staining for selectin ligands was also seen in goblet cells of normal colonic epithelium, the polarity and fate of these cells (eventually shed into the lumen of the gut) assures that these ligands would never be exposed to the vascular compartment in the normal situation.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant selectin immunoglobulin-Fc fusion proteins (selectin-Igs) were prepared and purified as reported. 19,51 For some experiments, we used selectin-Ig proteins incorporating the FLAG epitope tag (Eastman Kodak; details of these constructs will be reported elsewhere). The ␣2-3 linkage specific sialidase L was a kind gift from Dr. Y.-T. Lee of Tulane University (New Orleans, LA).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%